Indocyanine Green Lymphography for Evaluation of Breast Lymphedema Secondary to Breast Cancer Treatments - Yamamoto, Takumi; Yamamoto, Nana (Journal of Reconstructive Microsurgery, 2022)
Background Although breast lymphedema (BL) significantly deteriorates quality of life (QOL) of breast cancer survivors, little is known and pathophysiological severity staging system is yet reported. This study aimed to evaluate usefulness of a novel BL severity staging system based on indocyanine green (ICG) lymphography findings.Methods Breast cancer survivors with breast symptoms who underwent breast ICG lymphography were included. Breast ICG lymphography stage was determined based on visibility of linear pattern and extension of dermal backflow patterns. Prevalence of breast symptoms and lymphedema QOL score (LeQOLiS) was compared according to the stage.Results Thirty-seven patients were included. Breast ICG lymphography stage included stage 0 in 11 (29.7%) cases, stage I in 3 (8.1%) cases, stage II in 11 (29.7%) cases, stage III in 6 (16.2%) cases, stage IV in 4 (10.8%) cases, and stage V in 2 (5.4%) cases. Higher ICG stages were associated with more frequent prevalence of breast swelling (p = 0.020), breast pain (p = 0.238), and breast cellulitis (p = 0.024), and with higher LeQOLiS (p < 0.001).Conclusion ICG lymphography allows clear visualization of superficial lymph circulation in the breast. Higher breast ICG lymphography stages are associated with more frequent prevalence of BL-related symptoms and worse QOL.
Keywords: lymphedema; indocyanine green; breast cancer; supermicrosurgery; anastomosis